TG02, a novel oral multi-kinase inhibitor of CDKs, JAK2 and FLT3 with potent anti-leukemic properties - Goh, K C; Novotny-Diermayr, V; Hart, S; Ong, L C; Loh, Y K; Cheong, A; Tan, Y C; Hu, C; Jayaraman, R; William, A D; Sun, E T; Dymock, B W; et al. (Leukemia, 2012)
TG02 is a novel pyrimidine-based multi-kinase inhibitor that inhibits CDKs 1, 2, 7 and 9 together with JAK2 and FLT3. It dose-dependently inhibits signaling pathways downstream of CDKs, JAK2 and FLT3 in cancer cells with the main targets being CDKs. TG02 is anti-proliferative in a broad range of tumor cell lines, inducing G1 cell cycle arrest and apoptosis. Primary cultures of progenitor cells derived from acute myeloid leukemia (AML) and polycythemia vera patients are very sensitive to TG02. Comparison with reference inhibitors that block only one of the main targets of TG02 demonstrate the benefit of combined CDK and JAK2/FLT3 inhibition in cell lines as well as primary cells. In vivo , TG02 exhibits favorable pharmacokinetics after oral dosing in xenograft models and accumulates in tumor tissues, inducing an effective blockade of both CDK and STAT signaling. TG02 induces tumor regression after oral dosing on both daily and intermittent schedules in a murine model of mutant-FLT3 leukemia (MV4-11) and prolongs survival in a disseminated AML model with wild-type FLT3 and JAK2 (HL-60). These data demonstrate that TG02 is active in various models of leukemia and provide a rationale for the ongoing clinical evaluation of TG02 in patients with advanced leukemias.